A high voltage Li-ion full-cell battery with MnCo2O4/LiCoPO4 electrodes. Issue 16 (November 2020) - Islam, Mobinul; Akbar, Muhammad; Ali, Ghulam; Nam, Kyung-Wan; Chung, Kyung Yoon; Jung, Hun-Gi
Abstract: A new full-cell is reported herein that combines a high capacity conversion-type anode and an olivine-type 5 V cathode to develop a high energy Li-ion battery. The MnCo2 O4 anode was prepared through a simple solvothermal process followed by a post-annealing treatment. The synthesized MnCo2 O4 exhibited characteristic morphology consisting of spherical microspheres constructed from nanoflake units. The olivine-type LiCoPO4 cathode was synthesized by a rapid single-step microwave-assisted solvothermal approach using a 1:1 (v/v) ethylene glycol/water binary solvent mixture and sucrose as the reducing agent. After structural characterization of the electrodes by X-ray diffraction, their electrochemical response characteristics related to the lithium insertion/extraction in half-cells and those of the MnCo2 O4 //electrolyte (1 M LiPF6 in EC/DMC (3:7))//LiCoPO4 full-cell were analyzed. The highest reversible capacity of MnCo2 O4 and LiCoPO4 electrodes was 1167 and 107 mAh g −1, respectively, at 0.1 C-rate. The combination of these two electrodes produced a battery with an operating voltage of 4.2 V and a reversible capacity of 95 mAh g −1 at 0.1C, leading to an energy density of 415 Wh kg −1 based on the cathode mass. These results indicate that the MnCo2 O4 is a promising anode for high-performance lithium-ion batteries. Graphical abstract: Image 1